Coccolithophore paleoproductivity since the Last Glacial Maximum in the Atlantic Ocean: Relationship with calcification and preservation variability - Argenio, Carmen; Flores Villarejo, Jos? Abel; Fuertes Prieto, Miguel ?ngel; Balestra, Barbara; Amore, Filomena (Quaternary International, 2023)
[EN]Paleoproductivity, calcification and preservation patterns are presented from calcareous nannoplankton paleoassemblages records covering the last ~25 kyr retrieved from Integrated Ocean Drilling Program Sites U1385 (37?34.285? N; 10?7.562?W) and U1313 (41?0.0? N; 32?57.4? W), located respectively along the Western Iberian Margin and in the North Atlantic Ocean. The main aim of the study is to provide paleoceanographic and paleoclimatic analyses together with an investigation of changes in coccolithophore calcification processes occurring in response to climate variability from the Last Glacial Maximum up to the Holocene. Coccolithophore calcification was investigated by comparing variations in coccolith thickness and total coccolith calcite; at the same time dissolution/preservation indices were used to better understand the response of coccolithophores to changes in environmental parameters. In general, the increasing CO2 recorded during the last 25 kyr has a negative effect on calcification, resulting in a reduction of the different species size-normalized thicknesses at both sites. However, differences between the responses at the two latitudes studied are identified, in particular during the Heinrich Stadials; in contrast, during both Younger Dryas and Holocene intervals, the different size-normalized species thicknesses show consistent patterns at the two sites. During the Last Glacial Maximum the influence of subtropical waters due to Azores Current recirculation leads to a moderate productivity, initially at Site U1385 and later at Site U1313. At the same time, temperature influences the calcification at both sites. At Site U1385, the temperature is the main parameter affecting the paleoproductivity during Heinrich Stadial events; in addition, during Heinrich Stadial 1 alone, it also affects the calcification. At Site U1313 the calcification processes during Heinrich Stadial events are apparently hampered by an increasing water turbidity, caused by icebergs acting as ice rafted debris transporters, ...